PENGARUH ORIENTASI PASAR, KEWIRAUSAHAAN, DAN INOVASI TERHADAP KINERJA BISNIS PADA PERUSAHAAN ASPAL-BETON (HOTMIX) DI JABODETABEK - I Made Sukaryawan (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The purpose of this study was to research the influence of the marketorientation on the alternative strategic orientations and their impact on businessperformance onasphalt concrete companies in the city of Jabodetabek (Jakarta, Bogor,Depok, Tangerang, Bekasi), Indonesia. Alternative strategic orientations in this study ismarket, innovation, and entrepreneurial orientations. This research is associative causalrelationship to determine a causal relationship between the independent variable,market orientation, entrepreneurial orientation, intermediate variables, innovationorientation, and dependent variable, business performance. Instrument in this studyused a questionnaire for 30 respondents. Data processing techniques using the PartialLeast Square (PLS) program. The results of the PLS analysis shows effect of marketorientation, and entrepreneurial orientationon innovation orientation, and directimpactof market orientation, and entrepreneurial orientation on business performancegives the figure a significant correlation. Effect of innovation orientation onbusinessperformance gives the figure a significant correlation .Key words: Market orientation, Innovation Orientation, Entrepreneurial Orientation,Business Performance, and PLS.